Sistem maklumat kesihatan dan pengurusan gimnasium / Mazuin Mohd - Mazuin , Mohd (2004)
This project named Health Information System and Gymnasium Management. It is a web-based project that tends to be an informative concerning from time to time. Tills information system will be developing to fulfill the users requirement in data gathering and information searching in health topic especially on cardiovascular disease (CVD). It is a dynamic information system where all the information given will increase and be updated from time to time so that the user will have the most effective communication with the informative system. This system has two major parts that is Health Information System and Gymnasium Management System. Health Information System give the user at the information they want to know about the CVD like what is the causes, what is the risk, how to prevent it and what are the major type of CVD while the Gymnasium Management System is a system that will help the owner of the gymnasium to manage their databases that contents an information about the member, facilities etc. The major causes why I choose to develop this system is because there are no such system in our country and I think that it will help the user a lot to gain some information about gymnasium equipment before they really enter a gymnasium. Since the internet is becoming more and more common nowadays, it is almost a necessity to include more health information pages with new features to assist users in their quest of finding the relevant information.